PENGARUH KEPUASAN GAJI DAN KOMITMEN ORGANISASI TERHADAP TURNOVER INTENTION (Studi pada tenaga Outsorscing di UMY) - Yayan Muaziz (MNJ 16 UMY 102, 2016)
This research aims to determine how much the influence of salary satisfaction and organizational commitment toward turnover intention on labour outsourscing in Universita Muhammadiyah Yogyakarta. The sampling methods which is used in this research is nonprobability sampling, named purposive sampling. The number of respondents for this research are as many as 112 respondents. This research used Structural Equation Modeling (SEM) run by AMOS 21 programme as the analysis tool. The result of this research proved that salary satisfaction has significant negative influence toward turnover intention. furthermore, the salary satisfaction has positive influence toward organizational commitment, which it is as intervenning variable or mediate the correlation between salary satisfaction toward turnover intention. Key words: salary Satisfaction, Organizational Commitment dand Turnover Intention